2015
DOI: 10.1136/gutjnl-2014-308943
|View full text |Cite
|
Sign up to set email alerts
|

Towards an HBV cure: state-of-the-art and unresolved questions—report of the ANRS workshop on HBV cure

Abstract: HBV infection is a major cause of liver cirrhosis and hepatocellular carcinoma. Although HBV infection can be efficiently prevented by vaccination, and treatments are available, to date there is no reliable cure for the >240 million individuals that are chronically infected worldwide. Current treatments can only achieve viral suppression, and lifelong therapy is needed in the majority of infected persons. In the framework of the French National Agency for Research on AIDS and Viral Hepatitis 'HBV Cure' program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
250
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 236 publications
(256 citation statements)
references
References 165 publications
2
250
0
4
Order By: Relevance
“…Several definitions of cure have been proposed following several international workshops. 241,242 A true cure may not be feasible because HBV DNA is integrated into the host genome. Furthermore, among persons who recovered from acute hepatitis B, viral cccDNA can still be detected in the liver explaining the reactivation of HBV replication when these 'recovered' persons are profoundly immunosuppressed.…”
Section: Future Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several definitions of cure have been proposed following several international workshops. 241,242 A true cure may not be feasible because HBV DNA is integrated into the host genome. Furthermore, among persons who recovered from acute hepatitis B, viral cccDNA can still be detected in the liver explaining the reactivation of HBV replication when these 'recovered' persons are profoundly immunosuppressed.…”
Section: Future Treatment Optionsmentioning
confidence: 99%
“…First phase clinical trials are ongoing for several of these agents. 241,243 Several potential target mechanisms for immune modulation to engender or restore HBV specific immune responses in conjunction with profound inhibition of HBV replication and HBsAg production to attain immunological control have been suggested. 241 Combinations of antiviral therapy targeting multiple steps in the HBV lifecycle that suppress viral replication and viral antigen production and immune modulatory therapy to restore immune response to HBV will likely be needed to achieve the goal of a HBV 'cure'.…”
Section: Future Treatment Optionsmentioning
confidence: 99%
“…Parmi les nouvelles molécules immunomodulatrices, les agonistes de TLR (Toll-like receptors) sont en cours d'essai (pour revue [42]). Leur combinaison avec les vaccins thérapeutiques et les molécules antivirales actuelles devraient permettre d'obtenir un contrôle soutenu et persistant du virus jusqu'au but final qui est l'élimination du virus du foie, de l'AgHBs du sérum, et la guérison [43]. ‡…”
Section: Référencesunclassified
“…Over time, more efficacious and safer NAs have been developed. These drugs are capable of (I) reducing or eliminating HBV DNA in sera; (II) inducing hepatitis B e antigen (HBeAg) negativity; (III) causing seroconversion to antibody to HBeAg (antiHBe); (IV) reducing or negativity of circulating HBsAg; (V) inducing production of antibodies to HBsAg (anti-HBs); (VI) ameliorating liver damage, and delaying progression to complications (such as LC and HCC) in some, but not all, patients with CHB (11)(12)(13)(14). However, long-term follow up revealed that treatment-induced HBeAg seroconversion with suppressed viral replication is not sustainable in considerable numbers of CHB patients.…”
Section: Therapy Of Chronic Hbv Infectionmentioning
confidence: 99%